Cohort Fertility and Couple Educational Pairing - Andersson, Linus; Nitsche, Natalie; Trimarchi, Alessandra; Jalovaara, Marika (Duke University Press, 2026)
Educational disparities in cohort fertility rates (CFRs) often serve as the starting point for analyzing socioeconomic drivers of fertility. Because most children are born to couples, the relationship between education and fertility is the compound of both partners’ education. Measuring both partners’ educational levels is generally considered superior to measuring one partner's educational level. Yet, no study has comprehensively analyzed cohort fertility by couples’ educational pairing. Using Finnish register data, we provide the first analysis of CFRs from the perspective of educational pairings. For the female birth cohorts of 1969–1975, we decompose the CFR by the educational pairing of the union in which the births occur. This novel measure complements previous work focusing on the incidence or instantaneous birth risks by educational pairing, as it draws on lifetime exposure to unions by educational pairings and birth rate within such unions. Our analysis reveals that the CFR in Finland, for the most recent cohorts from which such measures can be derived, is predominantly the result of births in educationally hypogamous or homogamous unions and in unions where at least one partner has tertiary education. In particular, the CFR of highly educated women is composed of births to couples in which the male partner is also highly educated.